2012
DOI: 10.1002/uog.10081
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of the population‐based approach to pregnancy dating: results from 23 020 ultrasound examinations

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
0
14
1
2
Order By: Relevance
“…12,26 These comparative studies found a clinically relevant gestational age-dependent EDD prediction bias of more than 4 days for our dating charts. 12 Such systematically skewed bias 23,24 could not be shown in the current study of second trimester HC dating. 12 Such systematically skewed bias 23,24 could not be shown in the current study of second trimester HC dating.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…12,26 These comparative studies found a clinically relevant gestational age-dependent EDD prediction bias of more than 4 days for our dating charts. 12 Such systematically skewed bias 23,24 could not be shown in the current study of second trimester HC dating. 12 Such systematically skewed bias 23,24 could not be shown in the current study of second trimester HC dating.…”
Section: Discussioncontrasting
confidence: 78%
“…Unfortunately, the comparison was based on biparietal diameter and femur length measurements, neither of which represent a recommended method HC for second trimester dating. 23,24 The pregnant women had been assigned and informed about an EDD based on a different term prediction model. Furthermore the EDD predictions based on our charts (biparietal diameter, femur length) were retrospectively applied to the population in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Small for gestational age (SGA) was defined as birth weight < 10 percentile and FGR as birth weight < 2.5 percentile, adjusted for gestational age and sex [23-25]. Fetal complications identified at the DFM consultation included fetal death, fetal distress (non-reassuring cardiotocographic finding or pathological blood flow in umbilical artery), poly- or oligohydramnios (as reported in clinical files), fetal weight estimate <−10% by ultrasound measurement or fetal malformations.…”
Section: Methodsmentioning
confidence: 99%
“…We used a strict definition of healthy pregnancy including normal outcome of a DFM-related examination, followed by spontaneous vaginal term delivery of a healthy infant with birth weight > 10 th percentile (adjusted for gestational age and sex, [23-25]), Apgar score ≥ 7 5min , absence of neonatal complication or transfer to the neonatal care unit, and normal findings of placental examination.…”
Section: Methodsmentioning
confidence: 99%
“…Det viser seg også at aldersestimatet fra eSnurra er det estimatet som samsvarer best med LMP-aldersestimatet i populasjonen, selv om de tradisjonelle modellene faktisk tar utgangspunkt i LMP i konstruksjonen 12 . Interessant nok kan man teste de to utviklingsstrategiene på uniformt fordelte data, og finner da at de gir tilnaermet identiske estimater for termin og alder.…”
Section: Tilbake Til Alderunclassified